Environmental Conservation NGOsand the Concept of Sustainable Development - Scherrer, Yvonne M. (Journal of business ethics, 2009)
On the background of the widely known and controversially discussed concept of sustainable development and the ever increasing influence of non-governmental organisations (NGOs) on social, environmental and economic issues, this article focuses on how NGOs, specialised in environmental protection and conservation issues, reacted to the holistic societal concept of sustainable development which aims at finding solutions not only to environmental, but also to social and economic issues. For this purpose, the article investigates whether and to what extent the sustainability concept has been adopted by three worldwide leading environmental conservation NGOs: Greenpeace International, WWF International and IUCN International. The research, conducted in early 2006, reveals that the three organisations integrated the sustainability concept to different degrees depending on the organisations’ dominant value set. The more an organisation is bound to the idea of environmental protection, the less it is inclined to adopt strategies stemming from the sustainability concept whose implicit value system contradicts a strong bio- or eco-centric position. This finding adds evidence to the assumption that the holistic sustainability concept is most likely to be reduced and adapted when addressed by a specialised societal actor such as an NGO. Such insight into the influence of value systems on the actual actions of pressure groups might also be valuable in the light of the ever increasing number of strategic partnerships between NGOs and the private sector. To be familiar with each others’ action-leading key assumptions can significantly contribute to establishing a sound basis for a fruitful and rewarding collaboration.